Trackless Trams and Emerging Economy Cities: Is it a Leapfrog Technology? - Ndlovu, Vinnet (Curtin University, 2021)
Rapid innovation and development of modern technology has brought about the opportunity for developing economies to technologically leapfrog. This research assesses literature to show how Trackless Trams (TTs) could enable emerging cities to technologically leapfrog in a way that can enable multiple development objectives including the SDG’s. The research investigates the localisation of the SDGs and evaluates how the adoption of leapfrog technology especially TTs could enable a developing city like Bulawayo attain its SDGs.